Bikini open - Jeturian, Jeffrey; Seiko Films (Quezon City Seiko Films, 2005)
Go-getter Susan, an investigative TV host desperate for higher TV rating, exposes not only what goes behind the pageant but even the most private lives of the aspiring contestants. Gail- a wannabe movie star, Lara- the overachieving perfect girl and a Binibining Pilipinas beauty contestant hopeful, Sonny-the hunky playboy gym instructor and Bily a would be singer in search of his real father. These contestants along with 18 other pairs of male and female aspirants, their families sponsors, benefactors, managers, judges, hosts, organizers, and even the audience take us not just in the front seat but even behind the scenes for an examination of the bikini contest phenomenon.
VCD
Directed by Jeffrey Jeturian.
Cherry Pie Picache, Daiana Zubiri, Francine Prieto
Keywords: Feature films